Brief Cognitive Screening Tools for Dementia in Low-Educated Population from South America: A Systematic Review - Diego Chambergo-Michilot; Nilton Custodio; Rosa Montesinos; Belen Custodio; Nelson Luis Cahuapaza-Gutierrez; Paulo Caramelli; Ismael Luis Calandri; Sonia Maria Dozzi Brucki; Claudia Kimie Suemoto; Ricardo Allegri; SLACHEVSKY CHONCHOL, ANDREA MARÍA; José F. Parodi (S. Karger AG, 2025)
Introduction: Despite less education being common in Latin America, there is no systematic review on the use of brief cognitive screening (BCS) tools in illiterate and low-educated adults in the region. We systematically reviewed brief cognitive tests used to identify dementia in illiterate or low-educated adults from South America (SA). Methods: A systematic review was conducted according to the PRISMA and Cochrane guidelines. We searched four major databases: PubMed, Scopus, Web of Science, and Embase, for studies up to September 2023, and included observational studies that reported at least sensitivity, specificity, area under the receiver operating characteristic (ROC) curve, positive predictive value, or negative predictive value of dementia screening tools in illiterate or low-educated (less than 6 years of education) adults from SA. Results: Most studies in samples with illiteracy or low education across SA used BCS tools adapted to the local population’s language. Seventeen tests were identified; among them, the Mini-Mental State Examination (MMSE) and Rowland Universal Dementia Assessment Scale (RUDAS) were the more common tools with good diagnostic accuracy in people with dementia. The sensitivity and specificity of reported BCS tools were at least 90%, and the area under the ROC curve was higher than 0.95. Conclusions: The cutoff points for detecting dementia in illiterates and the low-educated adult population of SA should be adjusted for most brief cognitive tests. Developing specific and sensitive cognitive batteries for our region for cognitive evaluation in low-educated/illiterate participants is mandatory, including specific functionality evaluation.